Evaluation of Potential Usage of Incremental-Type Rotary Encoder Application for Angle Sensing in Steering System - Sunarto Kaleg; Aam Muharam; M. Redho Kurnia; Abdul Hapid (National Research and Innovation Agency, 2014)
The main target of a steering system is that the driver can change vehicle trajectory in accordance with the desired direction. Power steering has become a standard feature in automobile. It provides assisting power when the driver turns the steering wheel. The well-known power steering types include; Hydraulic Power Steering (HPS), Electro - Hydraulic Power Steering (EHPS), and Electric Power Steering (EPS). EHPS or EPS uses an Electronic Control Unit (ECU) which is specific for each vehicle. The ECU should be able to regulate power of electric motor to provide corresponding assisting power for the steering wheel. Therefore ECU requires input signals, one of which is vehicle wheel angle that can be indicated from the vehicle steering wheel angle. Incremental type of Rotary Encoder (RE) is used in steering angle sensor on a minibus. RE specification used was 60 pulses per rotation and the minibus steering transmission specification is 3.5 round of right wheel off angle to the left wheel off angle. So we get the RE angular resolution 6ºper pulse and 105 number of pulses to half of the steering transmission ratio. Repeatability then tested against to a steering angle counter module. Testing is done with a test cycle consisting of 3 repetitions: condition center of the steering wheel, the steering wheel is turned to full right, then to the full left, then back to the right up to the steering wheel center. The results obtained 2 pulses deviation, or equivalent to 12º of steering angle.